Aortic Stiffness Hysteresis in Isolated Mouse Aortic Segments Is Intensified by Contractile Stimuli, Attenuated by Age, and Reversed by Elastin Degradation - De Moudt, Sofie; Leloup, Arthur; Fransen, Paul (Frontiers in Physiology, 2021)
Aim: Cyclic stretch of vascular tissue at any given pressure reveals greater dimensions during unloading than during loading, which determines the cardiac beat-by-beat hysteresis loop on the pressure-diameter/volume relationship. The present study did not focus on hysteresis during a single stretch cycle, but investigated whether aortic stiffness determined during continuous stretch at different pressure also displayed hysteresis phenomena. Methods: Aortic segments from C57Bl6 mice were mounted in the Rodent Oscillatory Set-up for Arterial Compliance (ROTSAC), where they were loaded and unloaded in a pressure range from 60 to 240 mm Hg, while subjected to continuous cyclic stretch with a constant PP of 40 mm Hg at high frequency of 10 Hz. Diastolic and systolic diameter, compliance and the Peterson elastic modulus (Ep), as a measure of aortic stiffness were measured. This was performed in baseline conditions and following contraction by 1 adrenergic stimulation with phenylephrine or by depolarization with high extracellular K+ in aortas of young (5 months), old (26 months) and segments treated with elastase. Results: In baseline conditions, diastolic/systolic diameters and compliance for a pulse pressure of 40 mm Hg were larger at any given pressure upon unloading (decreasing pressure) than loading (increasing pressure) of the segments. The pressure-aortic stiffness (Ep) relationship was similar in the loading and unloading direction and aortic stiffness hysteresis was absent. On the other hand, aortic stiffness hysteresis was evident after activation of the VSMCs with the1 adrenergic agonist phenylephrine and with depolarization by high extracellular K+, especially after inhibition of basal NO release with L-NAME. Aortic stiffness was significantly smaller in the unloading than in the loading direction. In comparison with young mice, old mouse aortic segments also displayed contraction-dependent aortic stiffness hysteresis, but hysteresis was shifted to a lower pressure range. Elastase-treated segments showed higher stiffness upon unloading over nearly the whole pressure range. Conclusions: Mouse aortic segments display pressure- and contraction-dependent diameter, compliance and stiffness hysteresis phenomena, which are modulated by age and VSMC-extracellular matrix interactions. This may have implications for aortic biomechanics in pathophysiological conditions and aging.